Effects of short term increase of intraocular pressure on optic disc cupping - Azuara-Blanco, A. (1998)
AIMS—To evaluate the effect of acute elevation of intraocular pressure (IOP) on optic disc cupping. METHODS—10 emmetropic and 10 myopic volunteers were included in this study. The cup area (CA) and cup volume (CV) of the optic disc were determined with the Heidelberg retina tomograph (HRT). After baseline determinations, a suction cup was used to increase the intraocular pressure (IOP) to 20-25 mm Hg above the baseline and HRT images were obtained. RESULTS—Baseline IOP was 13.5 (SD 1.3) mm Hg and 12.6 (2.6) mm Hg in the emmetropic and myopic groups, respectively. The IOP was elevated to 35.4 (3.3) mm Hg and 34.4 (2.5) mm Hg in the emmetropic and myopic groups, respectively. When compared with their baseline values, the cupping variables (CA and CV) were significantly increased (p<0.05) during the suction treatment in both emmetropic and myopic subjects. CONCLUSION—There was a significant enlargement in the optic disc cupping during the artificial increment of intraocular pressure in both emmetropic and myopic eyes. In non-glaucomatous eyes the optic nerve head has a partially dynamic topography dependent upon the level of IOP.   Keywords: optic disc; intraocular pressure; compliance; glaucoma